What happened to the public organization? A bibliometric analysis of public administration and organization studies - Vogel, Rick (2014)
Despite their common roots in the early theories of organization, public administration and organization studies have evolved separately. This article explores the conditions that favor and initiate the cross-boundary exchange of knowledge between these two fields. The study applies bibliometric methodology and advances standard methods of science-mapping by combining different levels of analysis in a two-mode network, drawing on citation data from 16 European and North American top journals in organization studies and public administration, spanning the period 2000 to 2010. None of the 18 clusters of current research extracted from these data can be traced in both organization studies and public administration, however closer analysis reveals two strong links between these fields and indicates that the boundaries between them are semipermeable, allowing the unidirectional, rather than bidirectional, transfer of knowledge from organization studies to public administration. This study argues for greater rapprochement between these two fields and suggests ways in which this could be achieved. - Reproduced.
Keywords: Organizations; Public administration